Clinically silent indolent T‐cell leukemia. Issue 1 (10th November 2018) - Janot, Clément; Feriel, Joffrey; Borie, Claire; Lefevre, Edouard; Bennaceur‐Griscelli, Annelise; Turhan, Ali G.; Aumont, Cédric
Key Clinical Message: The clinically silent, symptom‐free T‐cell prolymphocytic leukemia case that we report here confirms the major interest of the analysis of the blood smear as usual care of any emergent lymphocytosis. It also brings out the issue of the monitoring and follow‐up of this uncommon presentation. Abstract : The clinically silent, symptom‐free T‐cell prolymphocytic leukemia case that we report here confirms the major interest of the analysis of the blood smear as usual care of any emergent lymphocytosis. It also brings out the issue of the monitoring and follow‐up of this uncommon presentation.